Potencialidades turísticas que tiene la localidad de la hacienda la Virginia para desarrollar un turismo comunitario - Villacrés Acosta, Gino Paúl (2016)
The the locality of Hacienda la Virginia has potential tourist resources, the same ones that have a historical value and unique scenic beauty, which must be valued and disseminated in order to contribute to the tourist development of this area. The present work, Based on natural tourism resources, Cultural and complementary, Develops a methodology that determines tourism potential of the locality of the Hacienda la Virginia To develop community tourism. In such a way that real results were obtained on the valorization of the resources, which allowed them to be assessed on a physical, biological, cultural, sociocultural and infrastructure level, This result will serve as a tool for planning and managing sustainable tourism in the locality.